Chronology of the three-body dissociation of 8He. (12th February 2019) - Laurent, B; Marqués, F M; Angulo, C; Ashwood, N I; Borge, M J G; Bouchat, V; Catford, W N; Clarke, N M; Curtis, N; Freer, M; Hanappe, F; Kinnard, V; et al.
Abstract: The space and time configurations of the dissociation of 8 He into 6 He+ n + n, on C and Pb targets, have been explored simultaneously for the first time. The final-state interactions in the n - n and 6 He- n channels are successfully described within a model that considers independent emission of neutrons from a Gaussian volume with a given lifetime. The dissociation on C target exhibits a dominant sequential decay through the ground state of 7 He, consistent with neutrons being emitted from a Gaussian volume of r nn rms = 7.3 ± 0.6 fm with a n-n delay in the sequential channel of 1400 ± 400 fm/ c, in agreement with the lifetime of 7 He. The lower-statistics data on Pb target correspond mainly to direct breakup, and are well described using the n - n volume measured, without any n -n delay. The validity of the phenomenological model used is discussed.